2012
DOI: 10.1111/j.1523-1739.2012.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Exurban Development on Nest Predation and Predator Presence in the southern Appalachian Mountains (U.S.A.)

Abstract: In the eastern United States, land-use and climate change have likely contributed to declines in the abundance of Neotropical migrant birds that occupy forest interiors, but the mechanisms are not well understood. We conducted a nest-predation experiment in southern Appalachian Mountain forests (North Carolina, U.S.A.) during the 2009 and 2010 breeding seasons to determine the effects of exurban development and temperature on predator presence and the average number of days until eggs in an artificial nest wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Our results showed that Blue Jays increased in occurrence with mean temperature, and American Crows increased with building density and mean temperature (Table ). Lumpkin et al () found that nest predation rates increased at warmer, low鈥恊levation sites and as building density increased. They documented predation by corvids and a variety of mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Blue Jays increased in occurrence with mean temperature, and American Crows increased with building density and mean temperature (Table ). Lumpkin et al () found that nest predation rates increased at warmer, low鈥恊levation sites and as building density increased. They documented predation by corvids and a variety of mammal species.…”
Section: Discussionmentioning
confidence: 99%
“…There was a single paper that reported only a correlation coefficient (Lumpkin et al, 2012), which we used as our effect size. For all other papers we coded each nest as failed (0) or survived (1), ranked urbanization around the nest according to the five levels on an ordinal scale from the least to the most urbanized based on the urbanization scores assigned by us, and ran a Spearman rank correlation between these two variables for each study.…”
Section: Data Extractionmentioning
confidence: 99%
“…Opposums are regular mesocarnivore predators of bird nests (Staller et al 2005, Lumpkin et al 2012, Melville et al 2014) and they even prey on poultry (Amador-Alcala et al 2013), although they also eat fruits, invertebrates and other small vertebrates (Eisenberg 1989). The common opossum is sympatric with house finches in the area where birds were captured (Eisenberg 1989).…”
Section: Study Speciesmentioning
confidence: 99%